Sintesis dan Aplikasi CuSnO3 sebagai Katalis pada Proses Degradasi Zat Warna Methyl Orange dengan Metode Fotolisis - Putri, Tiara Jelita; Sanjaya, Hary; Budiman, Septian (Lembaga Yasin AlSys, 2024)
Research on the degradation of methyl orange dye using the photolysis method using a copper tin oxide (CuSnO3) catalyst has been carried out. The aim of this research is to see how catalyst activity influences variations in methyl orange degradation time, whether the addition of MEA (Monoethanolamine) is more effective for photocatalyst applications. In this research, a concentration of 10 ppm of methyl orange was used, 40 mL of which was degraded with a CuSnO3 catalyst of 0.05 grams. This degradation process involves treatments including CuSnO3 catalyst without MEA; 1 mL, 1.5 mL, and 2 mL MEA. The characterization used in this research is UV – VIS. The analysis results showed that the percentage of degradation without MEA at a time variation of 240 minutes was 64.43%, while at 1 mL it was 19.77%, 1.5 mL 16.92%, and 2 mL 20.91%.